A Comparison of Mtwo Rotary File with K-File on Negotiation of Second Mesiobuccal Canal in Maxillary First Molar: A Clinical Study - Honardar, Kiamars; Vesal, Nahal; Hamze, Faeze; Nazarimoghadam, Kiumars; Labaf, Hossein; Shakeri, Laila (Iranian Endodontic Journal, 2008)
INTRODUCTION: This study was carried out to compare the capability of K-files with Mtwo rotary file in terms of negotiation as well as depth of penetration in second mesiobuccal (MB2) canal of maxillary first molar. MATERIALS AND METHODS: A total of 32 MB2 canal of maxillary first molars having different root curvatures (not more than 30 degree) and root lengths were selected and then detected by K-file #10, #8 and #6. Based upon file penetration the samples were assigned into four groups. Group A: K-file #10 penetrate>2mm into coronal third, group B: K-file #10 could penetrate<2mm into coronal third, continue proceeding with #8 which had>2mm penetration, group C: K-files #10 and 8 could penetrate<2mm, continue proceeding with #6 for deeper penetration, and group D: Mtwo file #10/.04 was applied into all three above groups until resistance was felt. Finally, accurate working lengths at each group after K-file #10 insertions into the canal were determined radiographically. The mean depths of root canal penetration were analyzed statistically using Duncan test by SAS software (version 9.1) in GLM procedure. RESULTS: The mean of initial penetration for #10 Mtwo files was 19.16 mm, whilst it was 7.72 mm for K-File #6, 10.72 mm for K-File #8, and 12 mm for K-File #10. The difference between Mtwo rotary files and hand K-Files was statistically significant (P<0.01). CONCLUSION: Mtwo rotary files could be an efficient substitute for hand files to negotiate MB2 canal both more easily and rapidly. To our knowledge, it is the first time that a NiTi rotary file showed success in negotiation of any canal.